Mapping Racial Geographies of Violence on the Colonial Landscape - Waldron, Ingrid (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2022)
This paper unpacks the concept of “spatial violence” to examine the social justice dimensions of race, place, space, and the Indigenous and Black communities in Canada. The paper highlights the larger socio-spatial processes that create disproportionate exposure and vulnerability to the harmful social, economic, and health impacts of inequality in Indigenous and Black communities. It also argues that the lived experience of spatial violence and toxic exposure live together and that it is not possible to understand their impacts in Indigenous and Black communities in isolation. The paper also disrupts traditional notions of “the environment” that are centered on harmonizing cities and nature by highlighting the symbolic and materiality of space, especially with respect to how it harms Indigenous, Black and other racialized communities.